Parasitic Myoma: A Very Rare Case Report aAnd Review of Literature (Journal of Surgical Sciences, 2019)
A 32 years old unmarried women presented with periumbilical colickey abdominal pain which shiftted to the right iliac fossa with anorexia, vomiting and low grade fever. She had history of open myomectomy 4 years back for menorrhagia with multiple fibroids (myomas). On examination, the pointing sign, Rovsing's sign, McBurney's sign &Blumberg's sign were positive. Then she was diagnosed as a case of acute appendicitis. Ultrasonography revealed nothing significant. Appendicectomy was done through right Grid Iron incision. Appendix was found inflammed, swollen and there was collection of fluid in the peritoneal cavity. During closure, incidentally a solid mass about 5 >